A Solid Binding Matrix/Mimic Receptor-Based Sensor System for Trace Level Determination of Iron Using Potential Measurements - Ayman H. Kamel; Felismina T. C. Moreira; Tamara I. Silva; M. Goreti F. Sales (International Journal of Electrochemistry)
Iron(II)-(1,10-phenanthroline) complex imprinted membrane was prepared by ionic imprinting technology. In the first step, Fe(II) established a coordination linkage with 1,10-phenanthroline and functional monomer 2-vinylpyridine (2-VP). Next, the complex was copolymerized with ethylene glycol dimethacrylate (EGDMA) as a crosslinker in the presence of benzoyl peroxide (BPO) as an initiator. Potentiometric chemical sensors were designed by dispersing the iron(II)-imprinted polymer particles in 2-nitrophenyloctyl ether (o-NPOE) plasticizer and then embedded in poly vinyl chloride (PVC) matrix. The sensors showed a Nernstian response for [Fe(phen)3]2+ with limit of detection 3.15 ng mL−1 and a Nernstian slope of 35.7 mV per decade.